Survey of Judges on the Role of Courts in American Society, 1979 - Yankelovich, Skelly ([Verlag nicht ermittelbar], 1984)
This survey was conducted in order to obtain from judges their views and experiences regarding the role of courts in American society, specifically on issues of caseload management. From a sample representing five regions of the country, 104 federal and state judges were interviewed about their general work practices and performance in court over the year previous to August 1979. Variables describe the amount of time judges spent on routine judicial activities, characteristics of cases requiring excessive time, the mechanisms employed in the resolution of civil disputes, techniques for reducing or more expeditiously handling heavy caseloads, and suggestions for extra-judicial dispute settlement processes that could serve as alternatives to courts. Data are also available on each judge's legal education, legal experience, and personal background.